Side Chain Orientation of Tryptophan Analogues Determines Agonism and Inverse Agonism in Short Ghrelin Peptides - Nicke, Lennart (ChemMedChem, 2019)
We describe two synthetic amino acids with inverted side chain stereochemistry, which induce opposite biological activity. Phe(4) is an important part of the activation motif of ghrelin, and in short peptide inverse agonists such as KwFwLL‐NH(2), the aromatic core is necessary for inactivation of the receptor. To restrict indole/phenyl mobility and simultaneously strengthen the interaction between peptide and receptor, we exchanged the natural monoaryl amino acids for diaryl amino acids derived from tryptophan. By standard solid‐phase peptide synthesis, each of them was inserted into ghrelin or in the aromatic core of the inverse agonist. Both ghrelin analogues showed nanomolar activity, indicating sufficient space to accommodate the additional side chain. In contrast, diaryl amino acids in the inverse agonist had considerable influence on receptor signaling. Whereas the introduction of Wsf maintains inverse agonism of the peptide, Wrf shifts the receptor more to active states and can induce agonism depending on its introduction site.